About diet of Vipera ursinii (Bonaparte, 1835) in a central Apennine grassland landscape: what do they eat when orthoptera are not present? - Gabriele Achille; Andrea Brusaferro; Csaba Szabó; Nazzareno Polini (Acta Zoológica Lilloana)
Abstract: In this ecological study, the researchers applied themselves to understanding the diet of Vipera ursinii. This viper has a very short period of activity and has a fragmented range; it frequents similar habitats but at different altitudes. In view of its Italian distribution, this study dealt with mountain populations that frequent primary pastures above the forest line, from 1600 to 1850 m a.s.l. At these altitudes and latitudes, the snake is known as a large consumer of meadow orthoptera. The present work was carried out in the Apennines (central Italy), the subjects studied were handled and divided between juveniles and adults. The diet of this snake has never been studied in the areas covered by the following population, so the metapopulation in question is new data. The aim of the research is to identify and analyze the diet of Vipera ursinii even in a period of non-population of orthoptera using methods already in use. Observation of regurgitated material or faecal droppings obtained by non-invasive ventral palpation were the components that led the researchers to unprecedented conclusions for both the species and the snake group: the presence in the diet of new taxa such as ants, slug and caterpillar. This new knowledge may give a new perspective on this taxon that is potentially vulnerable to environmental changes due to environmental thermal alteration phenomena.